2008
DOI: 10.1007/s00414-008-0309-4
|View full text |Cite
|
Sign up to set email alerts
|

A GEP-ISFG collaborative study on the optimization of an X-STR decaplex: data on 15 Iberian and Latin American populations

Abstract: In a collaborative work carried out by the Spanish and Portuguese ISFG Working Group (GEP-ISFG), a polymerase chain reaction multiplex was optimized in order to type ten X-chromosome short tandem repeats (STRs) in a single reaction, including: DXS8378, DXS9902, DXS7132, DXS9898, DXS6809, DXS6789, DXS7133, GATA172D05, GATA31E08, and DXS7423. Using this X-decaplex, each 17 of the participating laboratories typed a population sample of approximately 200 unrelated individuals (100 males and 100 females). In this w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
92
1
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(111 citation statements)
references
References 25 publications
12
92
1
6
Order By: Relevance
“…Therefore, the aim of this work was to evaluate the potential forensic suitability of additional genetic markers to be included in the routine forensic casework toolbox. Regardless of LD, the results obtained with the X-InDel panel for accumulated power of discrimination in males and females, as well as the mean exclusion chances in duos and trios, were slightly lower than other studied InDels [26,34,35], X-STR [6,36,37], and X-SNPs [38,39], but comparable with the X-chromosomal 21-InDel panel proposed by Edelman et al [40].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Therefore, the aim of this work was to evaluate the potential forensic suitability of additional genetic markers to be included in the routine forensic casework toolbox. Regardless of LD, the results obtained with the X-InDel panel for accumulated power of discrimination in males and females, as well as the mean exclusion chances in duos and trios, were slightly lower than other studied InDels [26,34,35], X-STR [6,36,37], and X-SNPs [38,39], but comparable with the X-chromosomal 21-InDel panel proposed by Edelman et al [40].…”
Section: Discussionsupporting
confidence: 80%
“…The analysis of forensic parameters showed that the values obtained for PD F , PD M , MEC T , and MEC D for this panel were slightly lower than those of other InDels [26,34,35,41] or STR panels [6]. Nevertheless, due to the low mutation rates of InDels, this panel could be used as a complement in cases displaying few microsatellite transmission incompatibilities.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…PCR amplification of autosomal (AS) short tandem repeat (STR) markers was carried out using the PowerPlex 1 16 System (Promega) from December/2011 to February/2012; after that PowerPlex 1 18D System (Promega) was used from March to July and PowerPlex 1 21 System (Promega) from August to December of 2012. When necessary, 12 Y-STR (PowerPlex 1 Y System, Promega) and 10 X-STR [1] markers were analyzed. The latter were amplified as proposed by Martins et al [2].…”
Section: Methodsmentioning
confidence: 99%
“…O polimorfismo presente nesse cromossomo vem atraindo cada dia mais a atenção de pesquisadores. Inúmeros estudos na população brasileira demonstraram que vários marcadores moleculares situados no cromossomo X já são validados para uso forense, sendo que estes apresentam resposta no que tange sobre a variabilidade desses polimorfismos na população (CAINÉ et al, 2007;CAINÉ et al, 2010;GUSMÃO et al, 2009;LEITE et al, 2009;MARTINS et al, 2008a;MARTINS et al, 2009;MARTINS et al, 2010a;MARTINS et al, 2010b;PENNA et al, 2011;RODRIGUES et al, 2010;RODRIGUES et al, 2011;SILVA et al, 2010;TAVARES et al, 2008). Na rotina forense, os marcadores do tipo STR mais utilizados são os localizados nos cromossomos autossômicos e no Y (TOMAS et al, 2015).…”
Section: Características Do Cromossomo Xunclassified